Vertebroplasty for Osteoporotic Fractures with Spinal Canal Compromise - Hiwatashi, A. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Percutaneous vertebroplasty can aggravate spinal canal narrowing, especially in patients with preoperative retropulsion. The purpose of this study was to evaluate changes in spinal canal dimension during percutaneous vertebroplasty for osteoporotic fractures with retropulsion. MATERIALS AND METHODS: We reviewed all cases of osteoporotic vertebral fractures treated with vertebroplasty. Twenty-one patients (25 vertebrae) had a retropulsed fragment that compromised the dimension of the spinal canal on preoperative imaging. We measured the degree of retropulsion before and after vertebroplasty to evaluate changes in spinal canal dimension. We also evaluated pain, neurologic status, vertebral body height, and wedge angle. RESULTS: Mean retropulsion was 4.2 mm before and 4.4 mm after vertebroplasty. There was no statistically significant difference (P = .32). Mean increase in vertebral body height was 2.6 mm anteriorly, 1.7 mm centrally, and 0.3 mm posteriorly. Mean decrease in wedge angle was 4.7°. There were statistically significant improvements in height and wedge angle (P < .01). None of our patients developed new symptoms during vertebroplasty or thereafter. Twenty of 21 patients (95%) showed partial or complete immediate pain relief, whereas 1 patient did not improve. CONCLUSION: Vertebroplasty can be performed safely in patients with spinal canal compromise. This procedure can reduce pain, increase vertebral body height, and decrease wedge angle without worsening of retropulsion.